1998
DOI: 10.1002/pro.5560070122
|View full text |Cite
|
Sign up to set email alerts
|

Computation of electrostatic complements to proteins: A case of charge stabilized binding

Abstract: Recent evidence suggests that the net effect of electrostatics is generally to destabilize protein binding due to large desolvation penalties. A novel method for computing ligand-charge distributions that optimize the tradeoff between ligand desolvation penalty and favorable interactions with a binding site has been applied to a model for bamase. The result is a ligand-charge distribution with a favorable electrostatic contribution to binding due, in part, to ligand point charges whose direct interaction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 27 publications
2
87
0
1
Order By: Relevance
“…One possibility is that the receptor binding epitope of the CD loop in the wild type sequence normally provides an electrostatic balance of one net positive charge 88 EERRR 92 that is mimicked by the mutant sequence with Arg 90 . The importance of charge distribution in protein binding is recognized generally (35). Its role in IL-5 receptor recognition merits further investigation through an 4 S. Chen, S.-J.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that the receptor binding epitope of the CD loop in the wild type sequence normally provides an electrostatic balance of one net positive charge 88 EERRR 92 that is mimicked by the mutant sequence with Arg 90 . The importance of charge distribution in protein binding is recognized generally (35). Its role in IL-5 receptor recognition merits further investigation through an 4 S. Chen, S.-J.…”
Section: Discussionmentioning
confidence: 99%
“…Electrostatic interactions also play an important role in determining thermodynamics of binding; i.e., binding affinity (Novotny and Sharp, 1992;Fersht, 1993, 1995;Zhu and Karlin, 1996;Chong et al, 1998;Sheinerman et al, 2000;Norel et al, 2001;Rauch et al, 2002). Substrate binding allows the formation of (potentially) favorable charge-charge interactions between the substrate and target, as well as stabilizing specific salt-bridges and hydrogen bonds Fersht, 1993, 1995;Chong et al, 1998).…”
Section: Iib Biomolecule-ligand and -Biomolecule Interactionsmentioning
confidence: 99%
“…Substrate binding allows the formation of (potentially) favorable charge-charge interactions between the substrate and target, as well as stabilizing specific salt-bridges and hydrogen bonds Fersht, 1993, 1995;Chong et al, 1998). However, at the same time, charges on the molecular binding surface must shed their bound water in order to allow close binding.…”
Section: Iib Biomolecule-ligand and -Biomolecule Interactionsmentioning
confidence: 99%
“…The indirect interaction between the two members of this hydrogen bond would favor complex formation, since solvent would screen their favorable electrostatic interaction less in the bound state than in the unbound state. An important result of the work reported here is that energetics due to indirect effects are significant, though the importance of this term has generally not been recognized~Elcock & McCammon, 1996;Oberoi et al, 1996;Chong et al, 1998;Kangas & Tidor, 1998!. Summing each type of term for every group in the GCN4 leucine zipper~in a manner that counts each interaction once! showed that the electrostatic effect of complex formation is destabilizing because the unfavorable solvation term~24.0 kcal0mol!…”
Section: Resultsmentioning
confidence: 99%